Implementasi Pencegahan Penyakit Melalui Penyuluhan Kesehatan di Dusun Sapan untuk Menurunkan Angka Kesakitan (Morbiditas) - Setiatin, Sali; Trimasuti, Wahyu; Christinawati, Santy (Journal Pemberdayaan Masyarakat Indonesia, 2019)
This community service program aims to reports the result of community service concerning the implementation of diseases prevention through health education in Sapan to decrease morbidity.The method usage for the research is a quantitative method with a descriptive approach. Data collection techniques usage through observation, interviews, counseling and literature review related to the subject matter. The problem that were found from the research are : 1) The high rates of morbidity in Sapan Desa Sumbersari Kecamatan Ciparay Kabupaten Bandung, 2) The Lack of public knowledge about PHBS and public awareness will throw garbage in its place, 3) The unavailability of trash cans around the road. The suggestion given were: 1) The community needs to know and be aware of infectious and non-infectious disease and the application of PHBS, 2) Puskesmas needs to improve socialization and health education for the community, 3) The local goverment provides a trash cans on the roadside and garbage banks in each hamlet.